PERSEPSI GURU DAN SISWA TERHADAP PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI POLA BILANGAN JENJANG SMP - Epi Ratna Sari; Lutfiah Dwi Gatara; Ridho Agio Nesta; Teddy Alfra Siagian; Ratnah Lestary (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The purpose of this research is to find out how teachers and students perceive the development of learning media based on Android in the matter of definition sub-chapter number patterns, square number patterns, rectangular number patterns and triangular number patterns for class VIII junior high school students. In this study used a qualitative descriptive method. And on the results of the research obtained by the teacher's perception in the form of a value proportion 1) on the Basic Competency aspect of 60% in the appropriate category; 2) material aspects of 79% very feasible category; 3) the display aspect is 86% very decent category; 4) the language aspect obtains a value proportion of 88.5% in the very decent category. In addition, the perceived students obtained in the form of the proportion of value 1) on the material aspect of 76% very feasible category; 2) the display aspect is 77% very decent category; 3) the language aspect obtains a value proportion of 75% in the proper category. So that from the results of teacher and student perceptions it can be stated that the development of Android-based learning media is very feasible to be implemented in number pattern learning activities.